The Concept of the Role of Parents in the Application of Morality to Children (Study of Surah Luqman Verses 12-19 in Tafsir Al-Misbah) - Savira, Varadiba; Drajat, Amroeni (Academy of Education Journal, 2024)
Education is a process that humanizes humans. This concept shows that without strong morality, education will not be achieved. This article aims to analyze Surah Luqman verses 12-19, which contain important themes in moral education for children. This study uses a qualitative method with a literature study approach, relying on the interpretation text "al-Misbah" by M. Quraish Shihab as a data source. which helps in identifying important and relevant themes. The results of this study indicate that the concept of moral education in Surah Luqman includes monotheism, obedience to parents, and an invitation to do good and prevent bad deeds. This study also found three main points in moral education, namely: spiritual morals, individual morals, and social morals. This study contributes to a more contextual interpretation of children's education, which will face social realities in their future lives. The concept of amar ma'ruf is education that is oriented towards harmony, while nahi munkar is an educational effort to avoid communal conflict.